The control of prolactin secretion and the role of gonadotrophin releasing hormone in the production of concordant secretory spikes of luteinizing hormone and prolactin in the luteal phase of the menstrual cycle - Kaplan, Hilton (Division of Endocrinology and Diabetology, 2018)
The control of prolactin secretion is a complex interaction of peptides and neurotransmitters acting either in an inhibitory or stimulating way to effect final secretion of this hormone from the lactotrope cell in the anterior hypothalamus. These factors may act either directly on the lactotrope cell or indirectly by changing either dopamine restraint of prolactin secretion or by modulating peptide substances or neurotransmitters higher up in the hypothalamus. Gonadal steroids may also modulate the effect of peptides or dopamine at the level of the lactotrope. Prolactin's major role in the female rat is one of milk production post - partum, nurturing the young. It probably also has other physiological functions and may play a part in the menstrual cycle although this is controversial. Certainly, pulsatile secretion of prolactin during the menstrual cycle is well established and in the luteal phase this is concomitant with the secretion of luteinizing hormone. Theories explaining the synchronous surges seen during this phase of the menstrual cycle have been proposed and GnRH has been implicated in the genesis of the concordance of these secretory spikes. Using a potent GnRH antagonist an experiment was undertaken to establish the role of GnRH by blocking this hypothalamic peptide and observing the effect that this had on luteinizing hormone, prolactin and follicle stimulating hormone. In the first part of the thesis the control of prolactin secretion is reviewed. In the following section, an experiment was performed using a potent GnRH antagonist. A dose response curve was established for the antagonist action on LH. Then a twice maximum dose of this peptide was administered to three subjects in the midluteal phase of the menstrual cycle and the response of LH, prolactin and FSH was measured. The results indicate that although the GnRH antagonist significantly blocked LH secretory peaks, this action was not observed for either prolactin or FSH. This result is perhaps at variance with previous data which suggested that GnRH was responsible for concordant secretory spikes of LH and prolactin in the midluteal phase of the menstrual cycle.